2012
DOI: 10.1186/1475-2840-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic animal models for the evaluation of anti-diabetic agents

Abstract: Diabetes mellitus is a potentially morbid condition with high prevalence worldwide thus being a major medical concern. Experimental induction of diabetes mellitus in animal models is essential for the advancement of our knowledge and understanding of the various aspects of its pathogenesis and ultimately finding new therapies and cure. Experimental diabetes mellitus is generally induced in laboratory animals by several methods that include: chemical, surgical and genetic (immunological) manipulations. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 81 publications
4
77
0
4
Order By: Relevance
“…1 The International Diabetes Federation have recently indicated that 8.3% of adults worldwide (387 million people) have diabetes and the same organization predicts that by 2035 this figure will rise to nearly 600 million people. 2 Observational evidence from experimental and clinical studies indicates that oxidative stress is involved in both the pathogenesis and the complications of DM.…”
Section: Introductionmentioning
confidence: 99%
“…1 The International Diabetes Federation have recently indicated that 8.3% of adults worldwide (387 million people) have diabetes and the same organization predicts that by 2035 this figure will rise to nearly 600 million people. 2 Observational evidence from experimental and clinical studies indicates that oxidative stress is involved in both the pathogenesis and the complications of DM.…”
Section: Introductionmentioning
confidence: 99%
“…Induced models have been created through five methods: surgical removal of the pancreas, administration of the drug alloxan, administration of the drug streptozotocin (STZ), highgalactose diets, and laser or chemical damage to the eye [27,[35][36][37][38][39][40][41][42][43][44][45][46]. While all methods of induction are still studied today, the most common is STZ administration, as it results in the fastest rate of disease development [41].…”
Section: Induced Modelsmentioning
confidence: 99%
“…Pancreatectomy was observed as early as 1922 to increase blood sugar levels in dogs [35], and by 1968-1971, a technique of complete pancreatectomy in adult dogs had been developed to induce diabetes [36,37]. This technically difficult method is usually applied to large animals such as cats and monkeys [27].…”
Section: Pancreatectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of new drug requires an appropriate animal model and other environmental condition for treatment of diabetes. 8 The major objective of the present review is to bring collectively all different in vivo models and in vitro methods under one plane so that it may be useful to researchers who are seeking their experimental work on diabetes.…”
mentioning
confidence: 99%